OBSERVATIONS ON THE CRAB FISHERY OF MANGALORE COAST - George, P C; Nayak, K Ramesh (Indian Journal of Fisheries, 2011)
CONSIDERABLE quantities of crabs are caught in the inshore waters ofMangalore coast and from the river mouths of this zone during December-June period and these find a ready market in the towns. Crabs are broughtto Mangalore town from the Ullal estuary and from Kasatgod, Kumbla,Bengre and Mulki centres. The fishery is more active during February-April when fishing for the shoaling fishes reaches the waning period. Unlikein other towns in the south or in the north, crab meat is very much in demandin Mangalore. On estimation, it was found that as much as 22 tons of crabsare brought to Mangalore Webster market alone every season. It may bementioned that the total production for the Malabar coast was estimatedto be only about 23 tons (Chidambaram and Venkataraman, 1944), Crabmeat is also sold at as high a price as any other esteemed variety of fish atthis place unlike other centres where it does not fetch a high price.